1973
DOI: 10.1063/1.1661961
|View full text |Cite
|
Sign up to set email alerts
|

Theory and observations of polymer crystal thickening

Abstract: The thickening of polymer crystals during isothermal annealing is usually observed to be an irreversible process. Phenomenological laws that govern such processes take the form of simple proportionalities-flux being proportional to force. For polymer crystals, a thermodynamic force capable of driving the thickening phenomenon arises from the unequal free energies of the fold and lateral surfaces. By analogy with other irreversible phenomena, the rate of crystal thickening is taken to be proportional to the der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…The log t law well explains the thickening process at low temperatures but not that at high temperatures. Apparently the theory based on irreversible thermodynamics seems to cover the whole process over all the temperature range [12,13]. Leveling-off of long period on high temperature annealing (stage II) can be explained by this theory.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The log t law well explains the thickening process at low temperatures but not that at high temperatures. Apparently the theory based on irreversible thermodynamics seems to cover the whole process over all the temperature range [12,13]. Leveling-off of long period on high temperature annealing (stage II) can be explained by this theory.…”
Section: Discussionmentioning
confidence: 95%
“…Annealing process is essentially irreversible. From this point N 753 of view, the process was theoretically treated later in terms of the irreversible thermodynamics of nonequilibrium state [12,13]. However, some aspects of this thickening process, for example, a sudden increase in lamellar thickness at an extremely early stage of annealing, are not thoroughly studied either experimentally or theoretically.…”
Section: Introductionmentioning
confidence: 98%
“…Comparison of eq (6) with eq (2b) shows that they are identical in form except that RTm has replaced IlHd in eq (2b) -a manifestation of the different effects considered (entropy versus enthalpy). Although Flory did not consider the effect of crystal size on the melting temperature, such an effect is obtainable from his theory [see eq (14) of ref. [1]].…”
Section: Melting Temperature Of Lamellar Crystalsmentioning
confidence: 99%
“…For the tetrafluoroethylene-hexafluoropropylene random copolymers, annealing studies [14] have shown that the rate of annealing is determined by the under· cooling (T~" (X) -Tanneal); i.e., the crystal thickness of copolymers with different concentrations will thicken approximately at the same rate at equal undercoolings. The rate of annealing decreases exponentially as (T~" (X) -Tannea l) inc reases.…”
Section: Equation (19b) Suggests That Isothermal Plots Ofmentioning
confidence: 99%
“…Near T ~ leq increases exponentially against a baseline expressed by the l0 value, and the period z may be considered as T ~ R Ctransf ~ A I (7) where Al -(l,q(T)-lo) or (/~q(T) -IBL(T)) if the baseline has a slope different from zero. Figure 4 gives the values (E, K) determined for HDPE [17,18], LDPE with CF3 [19] and CH3 [20] as side-groups, and PET [21]. It results that the polarity of the crystallization process given by E, n > 0 remains the same as for crystallization from the melt.…”
Section: Direct Measuring Systemsmentioning
confidence: 85%